2022
DOI: 10.12775/jehs.2023.13.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision making on donating organs for transplantation in the opinion of the respondents - study using the CAWI method

Abstract: Introduction: Organ transplantation is a procedure of transferring living cells, tissues or organs within one organism or between two organisms. Despite the great achievements of transplantology and the legal basis regulating organ and tissue procurement and transplantation, there are still difficulties in overcoming social and psychological resistance related to this method of treatment and related to granting consent for organ donation. The aim of the study was to determine the knowledge of the factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The author's study showed that, according to 98.7% of the respondents, transplantation is a life-saving procedure. Similarly, studies by other authors have found that nurses who would donate their organs have higher expertise, knowledge of the irreversibility of brain death and better attitudes toward organ donation ( 20 , 21 ). Medical personnel support transplantation procedures because of their high awareness of the issue.…”
Section: Discussionmentioning
confidence: 73%
“…The author's study showed that, according to 98.7% of the respondents, transplantation is a life-saving procedure. Similarly, studies by other authors have found that nurses who would donate their organs have higher expertise, knowledge of the irreversibility of brain death and better attitudes toward organ donation ( 20 , 21 ). Medical personnel support transplantation procedures because of their high awareness of the issue.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, research shows that since some tissues or organs are perceived as sacred or as the very essence of humanity (brain, heart, blood, eyes), some people are afraid that it will not be treated with respect during the research or after an autopsy. For example, since religion affects peoples’ beliefs on brain death (Majchrowicz, 2022 ; Majchrowicz et al, 2021 ) it can negatively affect people’s attitude toward brain donation (Aramoana et al, 2020 ; Halverson & Ross, 2012 ; Hussen et al, 2017 ; Kowal et al, 2015 ; Kraft et al, 2018 ; Marmamula et al, 2022 ; Simon et al, 2017 ). This is in line with previous studies that demonstrated that while people are eager to donate blood, cancerous tissue, skin, bones or/and liver tissue left over after a medical procedure, the most controversial types of biosamples include: brain postmortem, eyes postmortem, human embryos and reproductive tissues (Boise et al, 2017 ; Goodson & Vernon, 2004 ; Lewis et al, 2013 ; Majchrowska et al, 2022 ; Merdad et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%